Co-operative Values, Institutions and Free Riding in Australia: Can It Learn from Canada? - Peetz, David (Relations industrielles / Industrial Relations, 2005)
While there is a strong logic favouring co-operation, it faces a central problem: the “free rider” or “cheat.” Collectives find ways of promoting norms of solidarity and seek regulation to prevent free riding. Around two-fifths of Australian employees covered by collective agreements are free-riding non-members. Evidence suggests that the recent growth of free riding reflects institutional changes and not the decline of co-operative values and the ascendancy of individualism. The Canadian solution to the cheating problem, which is the Rand formula, inspired Australian unions to introduce (excessive) “agency fees” into collective agreements. These were eventually stopped by the state. Alternative models include “social obligation fees”—provisions for employees covered by the agreement to make a contribution to a voluntary organization of their choice.